Isolate‐dependent use of claudins for cell entry by hepatitis C virus. Issue 1 (8th November 2013) - Haid, Sibylle; Grethe, Christina; Dill, Michael T.; Heim, Markus; Kaderali, Lars; Pietschmann, Thomas
<x xml:space="preserve">Abstract</x> Hepatitis C Virus (HCV) entry involves at least four cellular factors, including CD81, the scavenger receptor class B type I (SCARB‐1), occludin (OCLN), and claudin‐1 (CLDN1). In addition, CLDN6 and CLDN9 have been shown to substitute for CLDN1 as HCV entry factors in human nonliver cells. We examined the role of different CLDN proteins during HCV entry by using cell lines expressing either predominantly CLDN1 (Huh‐7.5) or CLDN6 (HuH6). Huh‐7.5 cells were susceptible to all tested HCV isolates, whereas HuH6 cells were only permissive to some viral strains. Silencing of CLDN6 in HuH6 cells revealed that these cells are infected in a CLDN6‐dependent fashion, and ectopic expression of CLDN1 or CLDN6 in 293T cells lacking endogenous CLDN expression confirmed that only some HCV strains efficiently use CLDN6 for infection. CLDN1‐specific neutralizing antibodies (Abs) fully abrogated infection of Huh‐7.5 cells by isolates that use CLDN1 only, whereas viruses with broad CLDN tropism were only partially inhibited by these Abs. Importantly, infection by these latter strains in the presence of anti‐CLDN1 Ab was further reduced by silencing CLDN6, suggesting that viruses with broad CLDN usage escape CLDN1‐specific Abs by utilization of CLDN6. Messenger RNA (mRNA) levels of HCV entry factors in liver biopsies of HCV patients infected with different genotype and with variable degree of liver fibrosis were determined. Uniformly high levels of CD81, SCARB‐1, OCLN, and CLDN1 mRNA were detected. In contrast, abundance of CLDN6 mRNA was highly variable between patients. Conclusion: These findings highlight differential CLDN usage by HCV isolates, which may evolve based on variable expression of CLDN proteins in human liver cells. Broad CLDN tropism may facilitate viral escape from CLDN1‐specific therapeutic strategies. (Hepatology 2014;58:24–34)